Skin-to-skin care in preterm infants receiving respiratory support does not lead to physiological instability. Issue 4 (17th January 2017) - Lorenz, Laila; Dawson, Jennifer A; Jones, Hannah; Jacobs, Susan E; Cheong, Jeanie L; Donath, Susan M; Davis, Peter G; Kamlin, C Omar F
Abstract : Objective: Providing skin-to-skin care (SSC) to preterm infants is standard practice in many neonatal intensive care units. There are conflicting reports on the stability of oxygen saturation (SpO2 ) during SSC, which may create a barrier to a wider implementation of SSC to infants receiving respiratory support. Regional cerebral oxygenation (rcO2 ) measured using near-infrared spectroscopy can serve as a surrogate parameter for cerebral oxygen delivery and consumption. We hypothesised that rcO2 during SSC would be similar to standard care in preterm infants receiving respiratory support. Design: Prospective observational non-inferiority study. Setting: Single tertiary perinatal centre in Australia. Patients: Forty preterm infants (median (IQR) of 27.6 (26.0–28.9) weeks' gestation) receiving respiratory support were studied on day 8 (5–18). Interventions: Ninety minutes of SSC, with infants in incubators acting as their own control. Parents and caregivers were blinded to the measurements. Main outcome measures: Mean difference in rcO2 between SSC and incubator care; as well as heart rate (HR), SpO2, fraction of inspired oxygen (FiO2 ) and temperature, were compared using a paired t-test. Results: rcO2 was similar during SSC (mean (SD) 74.9 (6.5)%)% compared with incubator care (74.7 (6.1)%, mean difference (95% CI) 0.2 (−0.8 to 1.1)%, p=0.71). No clinically important differences in HR, SpO2, FiO2 or temperature were observed in the whole cohort and by mode of respiratory support (endotracheal tube mechanical ventilation, continuous positive airway pressure and high-flow nasal cannulae). Conclusions: Cerebral oxygenation and other physiological measurements in ventilated preterm infants did not differ between SSC and incubator care. Trial registration number: 12615000959572.